2022
DOI: 10.1371/journal.pone.0268373
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics of the sabA, hofC, homA, homB and frpB-4 genes of Helicobacter pylori in different regions of China

Abstract: Background Helicobacter pylori (H. pylori) encodes numerous outer membrane proteins (OMPs), with considerable geographic heterogeneity and related to different clinical outcomes. This study aimed to investigate the distribution characteristics of five important OMP genes (sabA, hofC, homA, homB and frpB-4) in different regions of China. Materials and method A total of 266 strains were isolated from 348 stomach biopsy specimens in Shandong, Guangxi, Heilongjiang, Hunan, and Qinghai provinces. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The homA and homB gene profiles vary greatly based on the geographic origin of the strains ( 45 , 46 ). Previous studies have shown that homB is found more frequently than homA in East Asian strains ( 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The homA and homB gene profiles vary greatly based on the geographic origin of the strains ( 45 , 46 ). Previous studies have shown that homB is found more frequently than homA in East Asian strains ( 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…H. Pylori is estimated to affect about half of the world’s population and is considered a major cause of chronic gastritis and peptic ulcers. Eradication of H. Pylori infection improves wound healing, prevents recurrence, and reduces the incidence of H. Pylori -related gastric diseases [ 2 4 ]. According to previous studies, this bacterium is a risk factor for some oral diseases, such as periodontal diseases (PDs), canker sores, squamous cell carcinoma, tongue irritation and bad breath [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%